Ghanaian Mathematics Teachers use of ICT in Instructional Delivery (Global Journal of Human-Social Science, 2017)
Purpose The purpose of the study was to investigate the extent of ICT use among Ghanaian mathematics teachers in their instructional delivery Design methodology approach A cross-sectional survey design was adopted in the present study A stratified sampling technique was used to select 120 mathematics teachers from 24 public Senior High Schools SHS with 12 schools each located in the rural and urban areas respectively The study employed questionnaires in data collection Findings The findings of the study indicated the use of Word Processing Internet and Calculators as very high The study also revealed that mathematics teachers had favorable attitudes towards the use of ICT in teaching mathematics The study further showed that most teachers were competent in the use of ICTs such as Microsoft office word PowerPoint Excel and Calculators The findings showed that there is a positive correlation between mathematics teachers use of ICT and competences Research Limitations Implications In common with others the study is limited to public SHS mathematics teachers in the Central Region of Ghana The results may differ if replicated in private SHS and other geographies Practical implications A number of signi cant implications are drawn from this study for example using the Curriculum Research Development Division CRDD of the Ghana Education Service in collaboration with the related agencies in the Ministry of Education should carry out research to review critically the mathematics curriculum and revise the existing syllabus to explicitly state what ICT tools must be used and how it should be used in the teaching and learning process Social Implication The teaching institutions should endeavor to make the necessary provisions for more females to pursue mathematics in their pre-service education and also train them to develop the skills in ICT in order to integrate it in their instructional delivery Originality value The paper provides valuable insig
Keywords: teachers; mathematics; information communication technology; instructional delivery; senior high school (SHS)